Analysis of the Effect of Financial Reporting Aggressiveness on Tax Aggressiveness (An Empirical Study on Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange) - Teslatum, Irene; Dewi, Syahrina Noormala; Tupamahu, Kevin Hermanto (JENDELA PENGETAHUAN, 2025)
This study analyzes the influence of financial reporting aggressiveness on tax reporting aggressiveness in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. A quantitative approach using multiple regression analysis is employed to examine the relationship between these variables, aiming to understand the extent to which aggressive financial reporting affects companies' tendencies toward aggressive tax reporting. The research data is obtained from annual financial statements published on the official IDX website and analyzed using SPSS version 25 statistical software. The findings reveal that financial reporting aggressiveness has a significant effect on tax reporting aggressiveness, indicating that companies with more aggressive financial reporting are likely to engage in aggressive tax reporting to minimize their tax liabilities. These findings provide important insights for policymakers and tax authorities regarding the need for stricter oversight of companies in this sector to ensure compliance with financial and tax regulations.